2016
DOI: 10.1021/jacs.5b08436
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Glycosylation of Anomeric Sulfonium Ions

Abstract: Anomeric sulfonium ions are attractive glycosyl donors for the stereoselective installation of 1,2-cis glycosides. Although these donors are receiving increasing attention, their mechanism of glycosylation remains controversial. We have investigated the reaction mechanism of glycosylation of a donor modified at C-2 with a (1S)-phenyl-2-(phenylsulfanyl)ethyl chiral auxiliary. Preactivation of this donor results in the formation of a bicyclic β-sulfonium ion that after addition of an alcohol undergoes 1,2-cis-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
64
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 54 publications
5
64
0
Order By: Relevance
“…[23] For example, glycosylations of glucosyl donor (S)-24,p rotected with acetyl esters at C-3, and C-6, gave the corresponding glucosides as only the a-anomer.H owever,s imilar glycosylations with glucosyl donor 26,p rotected with benzyle thers gave no or very poor anomerics electivity (Table 2B,e ntries 1-3v s. 6, 7). [25] These calculations showed that the C-3 acyl group destabilizes the oxocarbenium ion in the S N 1p athway therebyp romoting the S N 2p athway,a sw as postulated in earlier reports. After activationo ft he imidate leaving group, low-temperature NMR clearlys howedt he b-sulfonium ion had formed on the basis of the H-1 chemical shift and coupling constant (Figure 2C)a nd the correlation of C-1a nd H-8 in the HMBC spectrum ( Figure 2D).…”
Section: First and Secondgeneration Chiral Auxiliariessupporting
confidence: 67%
See 1 more Smart Citation
“…[23] For example, glycosylations of glucosyl donor (S)-24,p rotected with acetyl esters at C-3, and C-6, gave the corresponding glucosides as only the a-anomer.H owever,s imilar glycosylations with glucosyl donor 26,p rotected with benzyle thers gave no or very poor anomerics electivity (Table 2B,e ntries 1-3v s. 6, 7). [25] These calculations showed that the C-3 acyl group destabilizes the oxocarbenium ion in the S N 1p athway therebyp romoting the S N 2p athway,a sw as postulated in earlier reports. After activationo ft he imidate leaving group, low-temperature NMR clearlys howedt he b-sulfonium ion had formed on the basis of the H-1 chemical shift and coupling constant (Figure 2C)a nd the correlation of C-1a nd H-8 in the HMBC spectrum ( Figure 2D).…”
Section: First and Secondgeneration Chiral Auxiliariessupporting
confidence: 67%
“…[25] Three auxiliary variants werep repared, containing either at hiophenyl,ether (29), phenyle ther (30)o rb enzyl (31)m oiety.T he Rand S-configured auxiliaries were prepared giving rise to six variants in total. [25] Changing the S-configuration to the Rconfiguration had the largest effect on the auxiliaries that are expected to perform neighboring group participation (thiophenyle ther (29)a nd phenyl ether (30)a uxiliaries) suggesting ar ole of the sulfonium/oxonium ion in the reaction pathway. The benzyl auxiliary cannots tabilize the oxocarbenium ion and hence glycosylation through this intermediate is expected in al ess selective manner.I ns ome cases however,b enzyl auxiliary containing donor 31 performed quite well, but the same is true for a donor protected with aC -2 benzyl( data not shown, a/b = 15:1 with acceptor A6).…”
Section: First and Secondgeneration Chiral Auxiliariesmentioning
confidence: 99%
“…[7] Oxidation of 7a/b (60-80 %) proceeded with moderate yields to provide 1 C 4 mannolactones 8a/b.F inally,t he compounds 8a/b were deallylated to afford glycosyl donors 9b/c. [12] However, 9c,w hich because of the high reactivity was activated at lower temperature (À78 8 8C), produced exclusively b-mannosides with both the primary and secondary acceptor (entries 5and 6).These results indicate that reactive intermediates other than the a-sulfonium ion are also important for the observed b-selectivity. Thed onors 9a-c were preactivated at low temperature (À78 8 8C, À40 8 8C respectively) with 1.0 equivalents of Tf 2 Oi nt he presence of 2,6-di-tert-butyl-4-methylpyridine (DTBMP) as ab ase.A ll donors were activated almost instantaneously and reactions with 9a and 9b were warmed to À20 8 8Cbefore addition of the acceptor.A se xpected, 9a produced mainly a-mannosides, presumably via a cis-decalin sulfonium ion intermediate (entries 1a nd 2).…”
Section: Angewandte Chemiementioning
confidence: 90%
“…[12] However,glycosylation with the mannosyl donor 9c [12] However,glycosylation with the mannosyl donor 9c …”
Section: Angewandte Chemiementioning
confidence: 99%
“…[13] Convergent strategies can focus either on a[ 4 + +4] or a[ 3 + +5] key coupling. [16,18] Accordingly,t he orientation of the anomeric leaving groups had only little effect on the diastereoselectivity of the glycosylation. The selective formation of five 1,2-cis-a-glucosidic bonds (a-D-Glu) is the most challenging aspect of the assembly of octasaccharide 2.M any oligo-and polysaccharides that contain 1,2-cis-O-glycosidic linkages are biologically important.…”
mentioning
confidence: 99%